Memoriae conseruandae causa facit. Memory and history as vehicles of construction of identities in the hispanic-visigothic kingdom of Toledo (endings VI century - beginnings VIII century) (De Rebus Antiquis, 2020)
Both Hellenistic as Late Antique authors stressed the importance of History as the keeper of ancestral traditions and the most recent events, all recovered, firstly, by his own personal memory that is immortalized by the manuscripts, became collective memory, and documents reported by the past. Both memory and History could serve as pathways to the development of an identity for political purposes or enhance the distinct identities of social groups according to their ancestors. We intend, in this study to analyze whether these perspectives can be found in the example of Hispano-Visigothic kingdom, with emphasis on the writings of John of Biclaro and Isidore of Seville.
Keywords: Late Antiquity; Memory; History; Identities; Hispano-Visigothic kingdom of Toledo